The Relationship of Sports to the Incidence of Injuries in Para Sports Athletes: A Systematic Review - Fadyah Khoirunnisa; Suryo Saputra Perdana (Universitas Negeri Surabaya, 2025)
Background: Para-sport, as a branch of sports for individuals with disabilities, has grown significantly as a platform for social inclusion and athletic achievement. However, sports activities inherently carry injury risks, which are amplified in para-sport due to physical limitations and adaptive equipment use. Methods: This study systematically reviewed injury patterns across various para-sport disciplines in multi-event competitions. Using the PRISMA framework, we analyzed 13 studies published in the last decade. Results: Results indicate that contact sports such as wheelchair basketball and rugby reported the highest injury prevalence, primarily acute injuries like shoulder dislocations and contusions. Non-contact sports such as para-swimming and para-throwing showed chronic injuries like tendinopathies due to repetitive movements. Key risk factors included biomechanical imbalances, intense training, and the use of adaptive devices. Conclusions The findings highlight the need for tailored injury prevention strategies, including biomechanical evaluation, rehabilitation programs, and ergonomic sports equipment design, to ensure athlete safety and enhance performance sustainability in para-sports.